EVI-LINHD, a virtual research environment for digital scholarly editing - Rio Riande, María Gimena del (2016)
This poster presents the structure and design of the VRE (VIRTUAL RESEARCH ENVIRONMENT)of LINHD, the Digital Innovation Lab at UNED (http://linhd.uned.es) and the first Digital Humanities Center in Spain. It focuses on the possibilities of a collaborative environment focused on a very realistic type of research: a non-English speaker, relatively new in DH technologies, which is keen on working in his project with his team, but has not a uniform team of researchers (that means, they have different levels of understanding DH technologies)Taking into account the language barrier that English may suppose for a Spanish-speaker scholar or student and the distance they may encounter with the data and organization of the interface (in terms of computational knowledge) while facing a scholarly digital edition or collection, LINHD?s VRE comes as a solution for the virtual research Spanish speaking community interested in scholarly digital work.